Sulfide composite electrolyte material and preparation method and application thereof

By coating sulfide electrolyte particles with lithium ion conductor nanomaterials and polymers, the material achieves high lithium ion conductivity and improved air stability, addressing the challenges of sulfide electrolytes in existing technologies and facilitating industrial-scale production.

CN119170860APending Publication Date: 2024-12-20STATE POWER INVESTMENT CORPORATION RESEARCH INSTITUTE

Patent Information

Application Number
CN202310729671.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing sulfide electrolytes suffer from poor air stability and high sensitivity to moisture, leading to structural damage and reduced lithium ion conductivity, which complicates synthesis, storage, and increases costs, hindering their commercialization.

Method used

A sulfide composite electrolyte material is prepared by coating sulfide electrolyte particles with a lithium ion conductor nanomaterial, polymer, and lithium salt, forming a coating layer that enhances air stability while maintaining high lithium ion conductivity.

Benefits of technology

The coating layer effectively isolates the electrolyte from air, preserving conductivity and improving air stability, making the process simpler, cost-effective, and suitable for industrial-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170860A_ABST
    Figure CN119170860A_ABST
Patent Text Reader

Abstract

The invention provides a sulfide composite electrolyte material and a preparation method and application thereof, the sulfide composite electrolyte material comprises an inner core and a coating layer, and the coating layer coats the inner core; the inner core is sulfide electrolyte particles, and the coating layer comprises a lithium ion conductor nano material, a polymer and a lithium salt. The sulfide composite electrolyte material is prepared by coating the surfaces of sulfide electrolyte particles with the coating layer with high lithium ion conductivity, so that the sulfide electrolyte membrane prepared from the sulfide composite electrolyte material has high lithium ion conductivity; and the coating layer on the surface effectively isolates the contact between electrolyte ions and air, so that the air stability of the sulfide electrolyte membrane is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid electrolytes, and in particular, relates to a sulfide composite electrolyte material and a preparation method and application thereof. Background Art

[0002] The worldwide decarbonization revolution continues to drive the construction of renewable energy networks in modern life. As the most important electrochemical energy storage technology, lithium-ion batteries have been expanded and deployed in emerging decarbonization areas such as transportation electrification and grid-scale energy storage systems. However, due to the use of a large amount of flammable organic liquid electrolytes in current commercial lithium-ion batteries, there are serious safety risks. All-solid-state lithium batteries that use solid electrolytes instead of organic liquid electrolytes have attracted widespread attention as an alternative to emerging lithium-ion batteries.

[0003] Existing solid electrolytes are mainly divided into three categories: sulfide, oxide, and polymer. Among them, sulfide electrolytes are considered to have the most potential for application due to their ultra-high lithium ion conductivity. However, most sulfide electrolytes have very poor stability in air and will react with H in the air. 2 O produces highly toxic H 2 S gas, resulting in structural damage and a rapid decrease in ion conductivity. In addition, this extremely sensitive property to moisture requires that the synthesis, storage, and transportation of the material must be carried out under strict anhydrous conditions, resulting in cumbersome and time-consuming post-processing. What is more worrying is that complex processing technology and atmosphere control will greatly increase the cost of industrial scale-up, thereby hindering the commercialization of sulfide electrolytes. At the same time, the current preparation of sulfide electrolyte membranes usually involves mixing sulfide electrolyte particles, polymers, and solvents to form a pseudoplastic slurry and then applying a coating process. However, due to the low lithium ion conductivity of the polymer, the conductivity of the sulfide electrolyte membrane drops sharply, seriously deteriorating the performance of the battery.

[0004] At present, the air stability of sulfide electrolytes is mainly improved by doping with soft acid elements such as As, Sb, Bi, etc. However, expensive metal elements not only increase the cost, but also cause the electrolyte conductivity to decrease to varying degrees. There is also a method of improving the hydrolysis resistance of sulfide electrolytes by coating a layer of air-stable polymers or oxides. For example, patent CN111129579A uses a hydrophobic polymer that does not conduct lithium as a coating layer to improve the air stability of sulfide electrolytes; patent CN106887638A uses an oxide with low ionic conductivity as a coating layer to improve the hydrolysis resistance of the electrolyte. However, the limited conductivity of the above-mentioned coating material severely limits the transmission of lithium ions inside the sulfide electrolyte, limiting the performance of its high lithium ion conductivity. Therefore, preparing an air-stable sulfide electrolyte membrane while maintaining high lithium ion conductivity has become an urgent problem to be solved. Summary of the invention

[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the embodiment of the present invention provides a sulfide composite electrolyte material and a preparation method and application thereof.

[0006] In a first aspect, an embodiment of the present invention provides a sulfide composite electrolyte material, comprising:

[0007] A core, wherein the core is a sulfide electrolyte particle;

[0008] The coating layer covers the core; the coating layer comprises lithium ion conductor nanomaterials, polymers and lithium salts.

[0009] In the embodiment of the present invention, a sulfide composite electrolyte material is prepared by coating a coating layer with high lithium ion conductivity on the surface of sulfide electrolyte particles, so that the sulfide electrolyte membrane prepared using the material not only has high lithium ion conductivity, but also because the surface coating layer effectively isolates the contact between electrolyte ions and air, thereby effectively improving the air stability of the sulfide electrolyte membrane.

[0010] In some embodiments, the sulfide electrolyte particles include Li 2 SP 2 S 5 , Li 10 G 2 S 12 , Li 10 SnP 2 S 12 , Li 6 PS 5 Cl, Li 6 PS 5 Br, Li 6 PS5 I. Li 5.3 PS 4.3 Cl 1.7 , Li 5.35 Ca 0.1 PS 4.5 Cl 1.55 and Li 6 PS 5 Cl 0.25 Br 0.75 At least one of, preferably Li 5.3 PS 4.3 Cl 1.7 ;

[0011] And / or, the particle size of the sulfide electrolyte particles is 1 to 8 μm.

[0012] In some embodiments, the lithium ion conductor nanomaterial includes Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 , Li 1.5 Al 0.5 Ge 1.5 P 3 O 12 , Li 5 La 3 Ta 2 O 12 、LiTi 2 (PO 4 ) 3 , Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 , Li 0.5 La 0.5 TiO 3 and Li 14 ZnGeO 4 At least one of, preferably Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 ; The size of the lithium ion conductor nanomaterial is 1 to 5 nm;

[0013] and / or, the polymer comprises at least one of polyacrylonitrile, polyethylene oxide, polyvinylidene fluoride, polymethyl methacrylate, polyvinylidene fluoride-hexafluoropropylene, nitrile rubber and styrene-butadiene rubber, preferably styrene-butadiene rubber;

[0014] And / or, the lithium salt includes at least one of lithium perchlorate, lithium hexafluorophosphate, lithium oxalate difluoroborate, lithium bis(trifluoromethylsulfonyl imide) and lithium bis(fluorosulfonyl imide), preferably lithium oxalate difluoroborate.

[0015] In some embodiments, the mass ratio of the polymer to the lithium ion conductor nanomaterial is (1-3): (97-99);

[0016] And / or, Li in the lithium salt + The molar ratio of the polyol to the polymer is 1:(1-16).

[0017] In some embodiments, the coating layer has a thickness of 5 to 10 nm.

[0018] In a second aspect, an embodiment of the present invention provides a method for preparing the above-mentioned sulfide composite electrolyte material, comprising the following steps:

[0019] S1, mixing lithium ion conductor nanomaterials, polymers, lithium salts and solvents in proportion to obtain a composite dispersion;

[0020] S2, coating the composite dispersion on the surface of sulfide electrolyte particles through a spraying process to obtain a sulfide composite electrolyte material.

[0021] The preparation method of the sulfide composite electrolyte material in the embodiment of the present invention has simple process, is easy to operate, does not require complicated production equipment, has low cost, is widely used, and is suitable for industrial-scale production.

[0022] In some embodiments, in step S1, the concentration of the composite dispersion is 5 wt% to 10 wt%;

[0023] And / or, the solvent comprises at least one of toluene, anisole, chlorobenzene, tetrahydrofluoran, acetonitrile, dimethylformamide and N-methylpyrrolidone, preferably chlorobenzene.

[0024] In a third aspect, an embodiment of the present invention provides a sulfide electrolyte membrane, comprising the above-mentioned sulfide composite electrolyte material.

[0025] In some embodiments, the thickness of the sulfide electrolyte membrane is 10-100 μm, preferably 10-30 μm.

[0026] The features and advantages described above for the sulfide composite electrolyte material are also applicable to the sulfide electrolyte membrane and will not be described in detail here.

[0027] In a fourth aspect, an embodiment of the present invention provides a method for preparing the above-mentioned sulfide electrolyte membrane, wherein the sulfide composite electrolyte material is subjected to hot rolling to obtain the sulfide electrolyte membrane.

[0028] In some embodiments, during the hot rolling, the speed of the rolling roller is 2 to 200 rpm, the temperature of the rolling roller is 100 to 300° C., and the number of rolling is 5 to 20 times.

[0029] In a fifth aspect, an embodiment of the present invention further proposes an all-solid-state lithium-ion battery, comprising a positive electrode, a negative electrode and a solid electrolyte layer, wherein the solid electrolyte layer is the above-mentioned sulfide electrolyte membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the first charge and discharge curve of the all-solid-state lithium-ion battery assembled using the sulfide electrolyte membrane prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.

[0032] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by those having ordinary skills in the field to which the present invention belongs.

[0033] In this article, the term "and / or" is merely a term used to describe the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent three situations: A exists alone, A and B exist at the same time, and B exists alone.

[0034] Where values ​​are described herein as a range, it should be understood that such disclosure includes disclosure of all possible sub-ranges within that range, as well as specific values ​​falling within that range, regardless of whether a specific value or a specific sub-range is explicitly stated.

[0035] An embodiment of the present invention provides a sulfide electrolyte membrane, comprising:

[0036] In a first aspect, an embodiment of the present invention provides a sulfide composite electrolyte material, comprising:

[0037] A core, wherein the core is a sulfide electrolyte particle;

[0038] The coating layer covers the core; the coating layer comprises lithium ion conductor nanomaterials, polymers and lithium salts.

[0039] In some specific embodiments, the sulfide electrolyte particles include Li2 SP 2 S 5 , Li 10 G 2 S 12 , Li 10 SnP 2 S 12 , Li 6 PS 5 Cl, Li 6 PS 5 Br, Li 6 PS 5 I. Li 5.3 PS 4.3 Cl 1.7 , Li 5.35 Ca 0.1 PS 4.5 Cl 1.55 and Li 6 PS 5 Cl 0.25 Br 0.75 At least one of, preferably Li 5.3 PS 4.3 Cl 1.7 ;

[0040] And / or, the particle size of the sulfide electrolyte particles is 1 to 8 μm, non-limiting examples are: 1 μm, 2 μm, 5 μm, 8 μm, etc. The inventors have found that by controlling the particle size of the inner core sulfide electrolyte particles within the above range, a sulfide electrolyte membrane with suitable thickness and ionic conductivity can be obtained; if the particle size of the sulfide electrolyte particles is too small, it will lead to difficulty in dispersion; if the particle size of the sulfide electrolyte particles is too large, it will affect the thickness of the final sulfide electrolyte membrane.

[0041] In some specific embodiments, the lithium ion conductor nanomaterial includes Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 , Li 1.5 Al 0.5 Ge 1.5 P 3 O 12 , Li 5 La 3 Ta 2 O 12 、LiTi 2 (PO 4 ) 3 , Li 1.3 Al 0.3 Ti 1.7 (PO4 ) 3 , Li 0.5 La 0.5 TiO 3 and Li 14 ZnGeO 4 At least one of, preferably Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 ; Further, the size of the lithium ion conductor nanomaterial is 1 to 5 nm, non-limiting examples include: 1 nm, 2 nm, 5 nm, etc.;

[0042] and / or, the polymer comprises at least one of polyacrylonitrile, polyethylene oxide, polyvinylidene fluoride, polymethyl methacrylate, polyvinylidene fluoride-hexafluoropropylene, nitrile rubber and styrene-butadiene rubber, preferably styrene-butadiene rubber;

[0043] And / or, the lithium salt includes at least one of lithium perchlorate, lithium hexafluorophosphate, lithium oxalate difluoroborate, lithium bis(trifluoromethylsulfonyl imide) and lithium bis(fluorosulfonyl imide), preferably lithium oxalate difluoroborate.

[0044] In some specific embodiments, the mass ratio of the polymer to the lithium ion conductor nanomaterial is (1-3):(97-99), non-limiting examples include: 1:97, 1:99, 2:97, 3:97, 3:98, 3:99, etc.;

[0045] and / or, Li in lithium salts + The molar ratio of the polyol to the polymer is 1:(1-16), non-limiting examples include: 1:1, 1:5, 1:8, 1:10, 1:12, 1:16, etc.

[0046] In some specific embodiments, the thickness of the coating layer is 5-10 nm, non-limiting examples include 5 nm, 8 nm, 10 nm, etc.

[0047] In a second aspect, an embodiment of the present invention provides a method for preparing the above-mentioned sulfide composite electrolyte material, comprising the following steps:

[0048] S1, mixing lithium ion conductor nanomaterials, polymers, lithium salts and solvents in proportion to obtain a composite dispersion;

[0049] S2, coating the composite dispersion on the surface of the sulfide electrolyte particles through a spraying process to obtain a sulfide composite electrolyte material.

[0050] In some specific embodiments, the concentration of the composite dispersion is 5wt% to 10wt%, non-limiting examples include 5wt%, 8wt%, 10wt%, etc. The inventors found that by controlling the concentration of the composite dispersion within the above range, the sulfide electrolyte particles can be completely coated; if the concentration of the composite dispersion is too high, the coating layer will be too thick; but if the concentration of the composite dispersion is too low, the coating will be incomplete, thereby affecting the conductivity and air stability of the sulfide electrolyte membrane.

[0051] In some specific embodiments, the solvent includes at least one of toluene, anisole, chlorobenzene, tetrahydrofluoran, acetonitrile, dimethylformamide and N-methylpyrrolidone, preferably chlorobenzene.

[0052] In a third aspect, an embodiment of the present invention provides a sulfide electrolyte membrane, comprising the above-mentioned sulfide composite electrolyte material.

[0053] In some specific embodiments, the thickness of the sulfide electrolyte membrane is 10 to 100 μm, non-limiting examples include: 10 μm, 20 μm, 50 μm, 80 μm, 100 μm, etc.; further, the thickness of the sulfide electrolyte membrane is preferably 10 to 30 μm, non-limiting examples include: 10 μm, 15 μm, 20 μm, 30 μm, etc.

[0054] In a fourth aspect, an embodiment of the present invention provides a method for preparing the above-mentioned sulfide electrolyte membrane, wherein the sulfide composite electrolyte material is subjected to hot rolling to obtain the sulfide electrolyte membrane.

[0055] In some specific embodiments, during hot rolling, the rotation speed of the pressure roller is 2 to 200 rpm, non-limiting examples include: 2 rpm, 10 rpm, 50 rpm, 100 rpm, 150 rpm, 200 rpm, etc.; the temperature of the pressure roller is 100 to 300°C, non-limiting examples include: 100°C, 150°C, 180°C, 200°C, 250°C, 300°C, etc.; the number of rolling times is 5 to 20 times, non-limiting examples include: 5 times, 8 times, 10 times, 15 times, 20 times, etc.

[0056] In a fifth aspect, an embodiment of the present invention further proposes an all-solid-state lithium-ion battery, comprising a positive electrode, a negative electrode and a solid electrolyte layer, wherein the solid electrolyte layer is the above-mentioned sulfide electrolyte membrane.

[0057] The technical scheme of the present invention is further described in detail below in conjunction with specific examples. Conventional instruments and equipment in the art are used in the following examples. The experimental methods without specific conditions in the examples are conventional methods and conventional conditions well known in the art, or methods and conditions recommended by manufacturers. Unless otherwise specified, the various raw materials used in the following examples are conventional commercial products, or can be prepared by known methods.

[0058] Example 1

[0059] This embodiment provides a method for preparing a sulfide electrolyte membrane, comprising the following steps:

[0060] S1, dissolving styrene-butadiene rubber and lithium difluoroborate oxalate in chlorobenzene at a molar ratio of 1:1 to obtain a mixed solution; 6.5 La 3 Zr 1.5 Ta 0.5 O 12 Add to the mixed solution (wherein, styrene-butadiene rubber and Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 The mass ratio of the two is 1:99), and the mixture is uniformly mixed to obtain a composite dispersion, wherein the concentration of the composite dispersion is 5wt%;

[0061] S2, the composite dispersion is coated on a Li-ion battery with a particle size of 5 μm by spraying. 5.3 PS 4.3 Cl 1.7 On the surface of the particles, the coating layer has a thickness of 5 nm, and a sulfide composite electrolyte material is obtained;

[0062] S3, hot rolling the sulfide composite electrolyte material at 300°C and a roller speed of 50 rpm. After rolling 5 times, a sulfide electrolyte membrane can be obtained. The thickness of the obtained sulfide electrolyte membrane is 21 μm.

[0063] The sulfide electrolyte membrane prepared in this embodiment is used as the solid electrolyte layer, and LiNi 0.5 Co 0.2 Mn 0.3 O 2 , Li 5.3 PS 4.3 Cl 1.7 , styrene-butadiene rubber and conductive carbon composite materials as positive electrodes, lithium metal as negative electrodes, assembled into all-solid-state lithium-ion batteries, and their typical charge and discharge curves are as follows: Figure 1 As shown. Figure 1 It can be seen that the charge cut-off voltage of the battery is 4.3V, the discharge cut-off voltage is 2.5V, and there is no obvious capacity decay during the discharge process, indicating that the prepared sulfide electrolyte membrane has a wide electrochemical window and stability.

[0064] Example 2

[0065] This embodiment provides a method for preparing a sulfide electrolyte membrane, comprising the following steps:

[0066] S1, dissolving styrene-butadiene rubber and lithium difluoroborate oxalate in chlorobenzene at a molar ratio of 1:1 to obtain a mixed solution; 6.5 La 3 Zr 1.5 Ta 0.5 O 12 Add to the mixed solution (wherein, styrene-butadiene rubber and Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 The mass ratio of the two is 2:98), and the mixture is uniformly mixed to obtain a composite dispersion, wherein the concentration of the composite dispersion is 6wt%;

[0067] S2, the composite dispersion is coated on a Li-ion battery with a particle size of 4 μm by spraying. 5.3 PS 4.3 Cl 1.7 On the surface of the particles, the coating layer has a thickness of 10 nm, and a sulfide composite electrolyte material is obtained;

[0068] S3, hot rolling the sulfide composite electrolyte material at 300°C and a roller speed of 50 rpm. After rolling 5 times, a sulfide electrolyte membrane can be obtained. The thickness of the obtained sulfide electrolyte membrane is 18 μm.

[0069] Example 3

[0070] This embodiment provides a method for preparing a sulfide electrolyte membrane, comprising the following steps:

[0071] S1, dissolving styrene-butadiene rubber and lithium difluoroborate oxalate in chlorobenzene at a molar ratio of 1:1 to obtain a mixed solution; 6.5 La 3 Zr 1.5 Ta 0.5 O 12 Add to the mixed solution (wherein, styrene-butadiene rubber and Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 The mass ratio of the two is 3:97), and the mixture is uniformly mixed to obtain a composite dispersion, wherein the concentration of the composite dispersion is 5wt%;

[0072] S2, the composite dispersion is coated on a Li-ion battery with a particle size of 2 μm by spraying. 5.3 PS 4.3 Cl 1.7 On the surface of the particles, the coating layer has a thickness of 15 nm, and a sulfide composite electrolyte material is obtained;

[0073] S3, hot rolling the sulfide composite electrolyte material at 300°C and a roller speed of 50 rpm. After rolling 5 times, a sulfide electrolyte membrane can be obtained. The thickness of the obtained sulfide electrolyte membrane is 17 μm.

[0074] Example 4

[0075] This embodiment provides a method for preparing a sulfide electrolyte membrane, comprising the following steps:

[0076] S1, dissolving styrene-butadiene rubber and lithium difluoroborate oxalate in chlorobenzene at a molar ratio of 8:1 to obtain a mixed solution; 6.5 La 3 Zr 1.5 Ta 0.5 O 12 Add to the mixed solution (wherein, styrene-butadiene rubber and Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 The mass ratio of the two is 2:98), and the mixture is uniformly mixed to obtain a composite dispersion having a concentration of 7wt%;

[0077] S2, the composite dispersion is coated on a Li-ion battery with a particle size of 7 μm by spraying. 5.3 PS 4.3 Cl 1.7 On the surface of the particles, the coating layer has a thickness of 5 nm, and a sulfide composite electrolyte material is obtained;

[0078] S3, hot rolling the sulfide composite electrolyte material at 300°C and a roller speed of 50 rpm. After rolling 5 times, a sulfide electrolyte membrane can be obtained. The thickness of the obtained sulfide electrolyte membrane is 19 μm.

[0079] Example 5

[0080] This embodiment provides a method for preparing a sulfide electrolyte membrane, comprising the following steps:

[0081] S1, dissolving styrene-butadiene rubber and lithium difluoroborate oxalate in chlorobenzene at a molar ratio of 16:1 to obtain a mixed solution; 6.5 La 3 Zr 1.5 Ta 0.5 O 12 Add to the mixed solution (wherein, styrene-butadiene rubber and Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12The mass ratio of the two is 1.5:98.5), and the mixture is uniformly mixed to obtain a composite dispersion having a concentration of 8wt%;

[0082] S2, the composite dispersion is coated on a Li-ion battery with a particle size of 7 μm by spraying. 5.3 PS 4.3 Cl 1.7 On the surface of the particles, the coating layer has a thickness of 5 nm, and a sulfide composite electrolyte material is obtained;

[0083] S3, hot rolling the sulfide composite electrolyte material at 300°C and a roller speed of 50 rpm. After rolling 5 times, a sulfide electrolyte membrane can be obtained. The thickness of the obtained sulfide electrolyte membrane is 20 μm.

[0084] Example 6

[0085] This embodiment provides a method for preparing a sulfide electrolyte membrane, comprising the following steps:

[0086] S1, dissolving styrene-butadiene rubber and lithium oxalodifluoroborate in chlorobenzene at a molar ratio of 1:1 to obtain a mixed solution; 6.5 La 3 Zr 1.5 Ta 0.5 O 12 Add to the mixed solution (wherein, styrene-butadiene rubber and Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 The mass ratio of the two is 2.5:97.5), and the mixture is uniformly mixed to obtain a composite dispersion having a concentration of 9wt%;

[0087] S2, the composite dispersion is coated on a Li-ion battery with a particle size of 8 μm by spraying. 5.3 PS 4.3 Cl 1.7 On the surface of the particles, the coating layer has a thickness of 10 nm, and a sulfide composite electrolyte material is obtained;

[0088] S3, hot rolling the sulfide composite electrolyte material at 300°C and a roller speed of 50 rpm. After rolling 5 times, a sulfide electrolyte membrane can be obtained. The thickness of the obtained sulfide electrolyte membrane is 23 μm.

[0089] Example 7

[0090] This embodiment provides a method for preparing a sulfide electrolyte membrane, comprising the following steps:

[0091] S1, dissolving styrene-butadiene rubber and lithium difluoroborate oxalate in chlorobenzene at a molar ratio of 1:1 to obtain a mixed solution; 6.5 La 3 Zr 1.5 Ta 0.5 O 12 Add to the mixed solution (wherein, styrene-butadiene rubber and Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 The mass ratio of the two is 1:99), and the mixture is uniformly mixed to obtain a composite dispersion, wherein the concentration of the composite dispersion is 5wt%;

[0092] S2, the composite dispersion is coated with Li with a particle size of 2 μm by spraying process. 5.3 PS 4.3 Cl 1.7 On the surface of the particles, the coating layer has a thickness of 5 nm, and a sulfide composite electrolyte material is obtained;

[0093] S3, hot rolling the sulfide composite electrolyte material at 300°C and a roller speed of 50 rpm. After rolling 10 times, a sulfide electrolyte membrane can be obtained. The thickness of the obtained sulfide electrolyte membrane is 11 μm.

[0094] Comparative Example 1

[0095] This comparative example provides a sulfide electrolyte membrane, which is obtained by directly converting Li 5.3 PS 4.3 Cl 1.7 The particles are pressed into films.

[0096] Comparative Example 2

[0097] This comparative example provides a method for preparing a sulfide electrolyte membrane, comprising the following steps:

[0098] S1, dissolving styrene-butadiene rubber and lithium difluoroborate oxalate in chlorobenzene at a molar ratio of 1:1 to obtain a mixed solution, wherein the concentration of the mixed solution is 5 wt %;

[0099] S2, the mixed solution is coated on a Li-ion battery with a particle size of 5 μm by spraying. 5.3 PS 4.3 Cl 1.7 On the surface of the particles, the coating layer has a thickness of 5 nm, and a sulfide composite electrolyte material is obtained;

[0100] S3, hot rolling the sulfide composite electrolyte material at 300°C and a roller speed of 50 rpm. After rolling 5 times, a sulfide electrolyte membrane can be obtained. The thickness of the obtained sulfide electrolyte membrane is 30 μm.

[0101] Comparative Example 3

[0102] This comparative example provides a method for preparing a sulfide electrolyte membrane, comprising the following steps:

[0103] S1, dissolving nitrile rubber and lithium bis(fluorosulfonyl)imide in acetonitrile at a molar ratio of 5:1 to obtain a mixed solution, wherein the concentration of the mixed solution is 5 wt %;

[0104] S2, the mixed solution is coated on a Li-ion battery with a particle size of 5 μm by spraying. 10 G 2 S 12 On the surface of the particles, the coating layer has a thickness of 6 nm, and a sulfide composite electrolyte material is obtained;

[0105] S3, hot rolling the sulfide composite electrolyte material at 300°C and a roller speed of 50 rpm. After rolling 5 times, a sulfide electrolyte membrane can be obtained. The thickness of the obtained sulfide electrolyte membrane is 40 μm.

[0106] Comparative Example 4

[0107] This comparative example provides a method for preparing a sulfide electrolyte membrane, comprising the following steps:

[0108] S1, dissolving polymethyl methacrylate and lithium perchlorate in acetonitrile at a molar ratio of 3:1 to obtain a mixed solution, wherein the concentration of the mixed solution is 5 wt %;

[0109] S2, the mixed solution is coated on a Li-ion battery with a particle size of 5 μm by spraying. 2 SP 2 S 5 On the surface of the particles, the coating layer has a thickness of 6 nm, and a sulfide composite electrolyte material is obtained;

[0110] S3, hot rolling the sulfide composite electrolyte material at 300°C and a roller speed of 50 rpm. After rolling 5 times, a sulfide electrolyte membrane can be obtained. The thickness of the obtained sulfide electrolyte membrane is 50 μm.

[0111] The conductivity test was performed on the sulfide electrolyte membranes prepared in Examples 1-7 of the present invention and Comparative Examples 1-4. The specific test process is as follows: at room temperature, the conductivity of each sulfide electrolyte membrane was tested using AC impedance analysis, and then each sulfide electrolyte membrane was exposed to an environment of room temperature and 30% humidity for 24 hours, and then subjected to a conductivity test. The air stability of the sulfide electrolyte membrane was determined by the change in conductivity. The test results are shown in Table 1.

[0112] Table 1

[0113]

[0114] As can be seen from Table 1, after exposure for 24 hours, the ionic conductivity of the sulfide electrolyte membranes prepared in Examples 1-7 of the present invention remains almost unchanged, which is mainly due to the fact that the coating layer on its surface can effectively isolate the electrolyte ions from the air, reducing the conductivity loss of the sulfide electrolyte membrane, so that it exhibits good air stability. In contrast, the sulfide electrolyte membrane without a coating layer in Comparative Example 1 and the sulfide electrolyte membranes prepared by adding no lithium ion conductor nanomaterials to the coating layer in Comparative Examples 2-4, after exposure for 24 hours, the ionic conductivity of the sulfide electrolyte membrane is reduced by 4 orders of magnitude, further indicating that the coating layer in the embodiments of the present invention can give the electrolyte membrane excellent air stability.

[0115] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0116] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A sulfide composite electrolyte material, characterized in that: include: A core, wherein the core is a sulfide electrolyte particle; A coating layer, wherein the coating layer covers the core; The coating layer comprises lithium ion conductor nanomaterials, polymers and lithium salts.

2. The sulfide composite electrolyte material according to claim 1, characterized in that The sulfide electrolyte particles include Li2S-P2S5, Li 10 GeP2S 12 , Li 10 SnP2S 12 , Li6PS5Cl, Li6PS5Br, Li6PS5I, Li 5.3 PS 4.3 Cl 1.7 , Li 5.35 Ca 0.1 PS 4.5 Cl 1.55 and Li6PS5Cl 0.25 Br 0.75 At least one of; And / or, the particle size of the sulfide electrolyte particles is 1 to 8 μm.

3. The sulfide composite electrolyte material according to claim 1, characterized in that The lithium ion conductor nanomaterial includes Li 6.5 Ln3Z 1.5 Ta 0.5 O 12 , Li 1.5 Al 0.5 Ge 1.5 P3O 12 、Li5La3Ta2O 12 、LiTi2(PO4)3、Li 1.3 Al 0.3 Ti 1.7 (PO4)3、Li 0.5 La 0.5 TiO3 and Li 14 At least one of ZnGeO4; the size of the lithium ion conductor nanomaterial is 1 to 5 nm; and / or, the polymer comprises at least one of polyacrylonitrile, polyethylene oxide, polyvinylidene fluoride, polymethyl methacrylate, polyvinylidene fluoride-hexafluoropropylene, nitrile rubber and styrene-butadiene rubber; And / or, the lithium salt includes at least one of lithium perchlorate, lithium hexafluorophosphate, lithium oxalate difluoroborate, lithium bis(trifluoromethylsulfonyl)imide and lithium bis(fluorosulfonyl)imide.

4. The sulfide composite electrolyte material according to claim 3, characterized in that The mass ratio of the polymer to the lithium ion conductor nanomaterial is (1-3):(97-99); And / or, Li in the lithium salt + The molar ratio of the polyol to the polymer is 1:(1-16).

5. The sulfide composite electrolyte material according to claim 1, characterized in that The coating layer has a thickness of 5 to 10 nm.

6. A method for preparing the sulfide composite electrolyte material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, mixing lithium ion conductor nanomaterials, polymers, lithium salts and solvents in proportion to obtain a composite dispersion; S2, coating the composite dispersion on the surface of sulfide electrolyte particles through a spraying process to obtain a sulfide composite electrolyte material.

7. The method for preparing the sulfide composite electrolyte material according to claim 6, characterized in that: In the step S1, the concentration of the composite dispersion is 5wt% to 10wt%; And / or, the solvent includes at least one of toluene, anisole, chlorobenzene, tetrahydrofluoran, acetonitrile, dimethylformamide and N-methylpyrrolidone.

8. A sulfide electrolyte membrane, characterized in that: The invention comprises the sulfide composite electrolyte material according to any one of claims 1 to 5 or the sulfide composite electrolyte material prepared by the method according to any one of claims 6 to 7.

9. The sulfide electrolyte membrane according to claim 8, characterized in that The thickness of the sulfide electrolyte membrane is 10 to 100 μm.

10. A method for preparing a sulfide electrolyte membrane according to claim 8 or 9, characterized in that: The sulfide composite electrolyte material is hot rolled to obtain the sulfide electrolyte membrane.

11. The method for preparing a sulfide electrolyte membrane according to claim 10, characterized in that: During the hot rolling, the speed of the rolling roller is 2-200 rpm, the temperature of the rolling roller is 100-300° C., and the number of rolling is 5-20 times.

12. An all-solid-state lithium-ion battery, comprising a positive electrode, a negative electrode and a solid electrolyte layer, characterized in that: The solid electrolyte layer is the sulfide electrolyte membrane according to claim 8 or 9.

Citation Information

Patent Citations

  • Composite solid electrolyte material, preparation method thereof, and all-solid-state lithium ion secondary battery containing electrolyte material

    CN106887638A

  • Sulfide solid electrolyte material, preparation method thereof and solid-state battery

    CN111129579A

Cited By

  • Sulfide composite electrolyte and preparation method and application thereof

    CN119650822A

  • A sulfide composite electrolyte and its preparation method and application

    CN119650822B